TADIB TO INCREASE OBEDIENCE BEHAVIOR OF JUNIOR HIGH SCHOOL MUHAMMADIYAH GODEAN STUDENTS - Ayatullah Kutub Hardew; Ayatullah Kutub Hardew (Universitas Pendidikan Indonesia, 2022)
One of important things in education is students’ obedience in class. Disobedience that is often done by students is certainly a problem in education. This study used quasi-experiment with single case experiment design. Sampling used purposive sampling technique. The number research subjek were 6 subjects. This study used the checklist behavioral observastion form. Analysis used visual inspection with conservatice dual-criteria (CDC). The results obtained in this study were a total of 17 chart of the research subjects stated systematically. This is because the six points on which to base the determination of systematic or not systematic treatment is above the trend line. There is only one chart are not systematic. Because, in this chart, the five points that determines the systematic or not systematic treatment is below the trend line. TADIB (Training Adab Murid yang Baik) can increase the frequency obedience behavior to the students of junior high school Muhammadiyah 1 Godean.